Implementasi Ekonomi Sirkular Melalui Platform Bisnis Digital - Hetifah Sjafudian; Nuzul Husnah; Siswanda H. Sumarto; Inta Budi Setya Nusa (JEMBA, 2026)
The global sustainability crisis caused by the linear economic model has resulted in 92.8% of material flows being wasted, while Indonesia faces a "food paradox" with household food waste reaching 14.7 million tons per year. This study aims to explore the technological mechanisms, success factors, and barriers to implementing a circular economy through digital business platforms between 2020 and 2026. This study uses a Systematic Literature Review (SLR) method compiled based on the PRISMA protocol using the Scopus database and Sinta 1 and 2 accredited journals. It was found that digital platforms operate 15 main mechanisms to integrate circular ecosystems. The use of Artificial Intelligence (AI) as a decision-making neural system can reduce waste by up to 26%, while the synergy of IoT and Blockchain strengthens material traceability and market trust. In Indonesia, platforms such as CIRCLE show great potential in addressing food inefficiencies, although they are still hampered by digital literacy and investment costs. This research is expected to provide strategic insights for academics, business practitioners, and policymakers in aligning technological innovation with cultural and regulatory transformation to maintain competitiveness in a resource-constrained global economy.